Effect of sodium hexametaphosphate and fluoride on dual-species biofilms of Candida albicans and Streptococcus mutans - Hosida, Thayse Yumi [UNESP]; Pessan, Juliano Pelim [UNESP]; Cavazana, Thamires Priscila [UNESP]; Sampaio, Caio [UNESP]; Monteiro, Douglas Roberto [UNESP]; Botazzo Delbem, Alberto Carlos [UNESP] (Taylor & Francis, 2021)
This study evaluated the effect of sodium hexametaphosphate (HMP), administered alone or in combination with fluoride (F), on dual-species biofilms of Streptococcus mutans and Candida albicans. Biofilms were treated with HMP solutions at 0.25%, 0.5% and 1%, alone or combined with F (0.05%), and compared by evaluating their structure and quantifying the colony-forming units (CFUs), metabolic activity, production of biomass and extracellular matrix components. All HMP-containing solutions were capable of reducing metabolic activity, the biofilm biomass, and the extracellular matrix components. Furthermore, the treatment with 1% HMP/F significantly reduced the CFUs of S. mutans, although it showed no effect on the CFUs of C. albicans, in the dual-species biofilms. In general, the combination of HMP and F influenced all the parameters analyzed from dual-species biofilms, except the CFUs of C. albicans.
Keywords: Biofilms; Candida albicans; fluorides; phosphates; Streptococcus mutans